2022
DOI: 10.1364/oe.451295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of color-enhancing glasses on color vision in congenital red-green color deficiencies

Abstract: As commercially available glasses for color vision deficiency (CVD) are classified as low risk, they are not subject to stringent marketing regulations. We investigate how EnChroma and VINO glasses affect performance on the Colour Assessment and Diagnosis (CAD) test in individuals with CVD. Data were obtained from 51 individuals with red-green CVD. Blood or saliva samples were collected to examine the structure of the OPN1LW/OPN1MW array. Individuals completed the CAD test twice without glasses and once with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Some studies have used digital tests for CVD. No significant effects of EnChroma filters have been found for the CAD test (Patterson et al, 2022), the CVA-UMinho test (Álvaro et al, 2022) or a computerized version of the Farnsworth-Munsell 100 hue test (Almutairi et al, 2017). However, small significant effects of Oxy-Iso filters have been reported for the CAD test (Patterson et al, 2022) and of EnChroma filters on computerized versions of the Ishihara Plates test (Almutairi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have used digital tests for CVD. No significant effects of EnChroma filters have been found for the CAD test (Patterson et al, 2022), the CVA-UMinho test (Álvaro et al, 2022) or a computerized version of the Farnsworth-Munsell 100 hue test (Almutairi et al, 2017). However, small significant effects of Oxy-Iso filters have been reported for the CAD test (Patterson et al, 2022) and of EnChroma filters on computerized versions of the Ishihara Plates test (Almutairi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…No significant effects of EnChroma filters have been found for the CAD test (Patterson et al, 2022), the CVA-UMinho test (Álvaro et al, 2022) or a computerized version of the Farnsworth-Munsell 100 hue test (Almutairi et al, 2017). However, small significant effects of Oxy-Iso filters have been reported for the CAD test (Patterson et al, 2022) and of EnChroma filters on computerized versions of the Ishihara Plates test (Almutairi et al, 2017). These positive effects have been interpreted as arising from luminance differences between target and distractor colors introduced by the filters (Patterson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral notches in the transmission spectra of EnChroma filters are designed to increase the difference between the signals of the cone types sensitive in the medium and long wavelength part of the spectrum by filtering out light in the spectral region where the cone sensitivity functions are most similar. However, thus far, there has been limited empirical support for their effectiveness, and several studies have concluded that they are largely ineffective (Álvaro et al, 2022;Gómez-Robledo et al, 2018;Patterson et al, 2022;Pattie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%